Relationship between Variations in the Circle of Willis and Flow Rates in Internal Carotid and Basilar Arteries Determined by Means of Magnetic Resonance Imaging with Semiautomated Lumen Segmentation: Reference Data from 125 Healthy Volunteers - Tanaka, H.; Fujita, N.; Enoki, T.; Matsumoto, K.; Watanabe, Y.; Murase, K.; Nakamura, H. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Volume flow rates in the feeding arteries of the brain are measured to evaluate blood flow dynamics in vascular disease. Although these flow values are thought to be effected by anatomic variations in the circle of Willis, few reports have described the effect. This study reports on the relationship between variations in the circle of Willis and volume flow rates in the bilateral internal carotid and basilar arteries of normal volunteers.METHODS: We prospectively examined 125 healthy volunteers by MR imaging. Variations in the circle of Willis were classified as “textbook” type, hypoplasia of the precommunicating segment of the anterior cerebral artery (A1), hypoplasia of the precommunicating segment of the posterior cerebral artery (P1), or “other.” Volume flow rates were measured by 2D cine phase-contrast MR imaging. Lumen boundaries and volume flow rates were semiautomatically determined by pulsatility-based segmentation.RESULTS: Of the 117 subjects (61 men, 56 women; mean age, 23.6 years) considered suitable for flow measurement, 105 showed textbook type, and 6 each showed A1 hypoplasia and P1 hypoplasia. Total flow rates for the 3 variations were 781 ± 151 mL/min (mean ± SD), 744 ± 119, and 763 ± 129, respectively. Relative contributions by flow rates of the internal carotid arteries and the basilar artery for the 3 variations were 39.8%:38.9%:21.3%, 31.8%:49.1%:19.0%, and 46.6%:41.6%:11.7%, respectively, showing statistically significant differences.CONCLUSIONS: Variations in the circle of Willis correlate significantly with relative contributions by the flow rates of the bilateral internal carotid and basilar arteries.